Human rights and control of personal data in the digital economy: EU legal case studies and recommendations for Vietnam - Trung Hau, Vo (Ius Humani. Jornal do direito, 2025)
Personal data is strictly managed and protected because it is a matter related to human rights. According to the European Union (EU) law, personal data control is a fundamental right recognized in the European Convention on Human Rights (ECHR) and the EU Charter of Fundamental Rights. Based on the analysis of the content of EU regulations on this issue, the article recommends improving Vietnamese law. The article recommends that Vietnamese law develops regulations on personal data protection in technology-neutral language. In addition, there should also be specific regulations explaining the term personal data. Accordingly, personal data includes not only information that can be linked or associated with a particular individual at the time the data are processed, but also all information that may be linked or associated with that individual during future processing, possibly by technological means that were not yet developed at the time the personal data were collected or generated.